Evaluasi Ketepatan Terapi Obat Pada Pasien Gagal Ginjal Di Instalasi Rawat Inap RSUD Dr. Moewardi Surakarta Tahun 2014 - Winalda, Gabela Ardavy, Dra. Nurul Mutmainah, M.Si., Apt (2016)
Kidney failure is a clinical condition characterized by the irreversible decline of kidney function. Decreased in kidney function leads to the accumulation of drug and its active metabolite, and this sometimes cause nephrotoxicity. This study was aimed to determine the accuracy of drug therapy including the right indications, the right patient, and the accuracy of drug selection and dosage for the inpatients with kidney failure at Dr. Mewardi Hospital Surakarta in 2014. This study is a non-experimental study with retrospective data collection and the data was analyzed using descriptive analysis method. The samples were taken from the medical records of the patients that meet the inclusion criterias of this study, i.e. patients with kidney failure hospitalized in July-December 2014, patients who received drug therapy, and patients who have a complete medical record. The results obtained from 53 samples and 308 drugs, indicated that several drugs which are commonly used in the treatment of the patients with kidney failure are furosemide 86.79%, calcium carbonate 77.35%, and folic acid 73.58%. Meanwhile, from 35 sample patients and 177 drugs, indicated that several drugs which are commonly used in the treatment of the patients with kidney failure on the hemodialisis are furosemide 85,71%, calcium carbonate 77,14%, and folic acid 74,28%. The accuracy of drug therapy based on the right indications 99.35%, the right patient 98.05%, the right drug 78.25%, the right dosage 50.32%, and the right dosage on the hemodialisis 65.53%.